Analisis Ekonomi Pengusaha Tempe dalam Menghadapi Kenaikan Harga Kedelai Impor di Kelurahan Semper, Jakarta Utara - Naelis Naelis; Novindra Novindra (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2015)
Soybean is one of the important agriculture commodities in Indonesia after rice and corn. The increasing domestic soybean consumption exceed its production. To fulfill domestic needs, Indonesia import the soybean. One of the industries that have a dependent to the imported soybeans is Tempe production. The rising prices of imported soybean caused the increasing price of production factor and affecting the revenue of Tempe entrepreneur. DKI Jakarta is one of the provinces that have a large population of Tempe industries and use the imported soybean as a raw material of its production. One of the regions is Semper, North Jakarta. The result of estimation factors that influenced the Tempe production is the amount of soybeans (kg/production process). The total cost of Tempe production is increasing 19,80 percent and the cash cost is increasing 19,89 percent. The revenue of the cash cost and total cost is decreasing 53,62 percent and 54,04 percent. The amount of R/C ratio upon the total cost after the rising prices of soybean is 1,19. The activity of Tempe production is still giving revenue although there is rising prices of the soybean because the revenue is positive and the amount of R/C ratio is more than one.